Changes in the abundance and diversity of soil arthropods in the cultivation of fruit crops - Araújo, Jackson; Pastori, Patrik; Gomes, Vânia Felipe; Mendes Filho, Paulo; Nunes, Luís Alfredo (Revista Ciência Agronômica, 2018)
The aim of this study was to evaluate the influence of fruit-crop management (mango, guava and coconut) on the composition and distribution of soil arthropods (mesofauna and macrofauna) during seasonal periods in the Curu Valley region of the State of Ceará, Brazil. The study was carried out during the following periods: rainy/dry (July/August 2013), dry (October/ November 2013), dry/rainy (January/February 2014) and rainy (April/May 2014). Pitfall traps were used to capture the arthropods. After sorting, the Shannon-Wiener diversity index and the Pielou evenness index were calculated. Diversity values were compared in pairs using Student’s t-test (α = 0.05) in the SAS v 9.0 software (2002). The similarity of the areas and groups was evaluated by multivariate analysis employing the techniques of principal component (PCA) and factor (FA) analysis in the Statistica® software (2014). The abundance and diversity of soil arthropods in the cultivation of fruit trees vary according to the type of management and to the seasonal period in the region. The Acari, Collembola and Formicidae groups were the most abundant in each area and during the four periods of the study. The area cultivated with coconut shows better soil conditions for maintaining the arthropod community in the soil.